The Influence of Formative Assessment Methods on Learning Outcomes of Plane Geometry by Controlling Critical Thinking Skills - I Putu Wisna Ariawan (AL-ISHLAH: Jurnal Pendidikan, 2022)
To improve the quality of student learning outcomes in plane geometry, aside from improving the quality of learning, it can also be done through improving the quality of the assessment. Therefore, the application of appropriate assessment methods in learning plane geometry is very important. This study aims to determine the effect of formative assessment methods (performance assessment and conventional assessment) on student learning outcomes in plane geometry by controlling critical thinking skills. This research is a quasi-experimental research involving 40 students majoring in Mathematics Education, FMIPA Undiksha as a sample. Data analysis was performed using one-way covariance analysis. By controlling critical thinking skills, the results of the study show that the learning outcomes of plane geometry of students who are given a performance assessment are higher than students who are given a conventional assessment.